Issues and challenges in Talent Identification (TID) programmed implementation : a case study in Johor / Mohamad Yusuff Awal and Jamiaton Kusrin - Awal, Mohamad Yusuff; Kusrin, Jamiaton (Faculty of Business Management, 2013)
The lacked of talents in sport among the new generation was made our country were left behind from another famous country that have been already ahead in conquering sport fields. Nowadays, various technologies may able to helping them in producing the greatest potential athletes in order to achieve their goal to win the gold medal in the world tournaments. Correct identification of athletic talent has many benefits. From an economic perspective, the success of the multibillion money professional sport industry relies heavily on successful identification and development of sport talent.